Plant Ornaments in The Architectural Details of Art Nouveau Townhouses And Villas in Sopot - Szumigała, Paweł Piotr; Szumigała, Karolina Olenia (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2022)
The article presents issues related to the use of floral ornaments in decorations and in detail of Art Nouveau tenement houses in Sopot. The research covered 2 and 3 storey buildings – 14 tenement houses and 4 villas. The research was aimed at isolating the characteristic and most commonly used plant motifs and fragments of the façade on which these motifs appeared. Comparisons of floral motifs and architectural details in iconographic form and in the form of tabular lists are presented. The results of the research indicate that the most frequently used characteristic plant motifs in Sopot are: the dominant acanthus, then field poppy and a group of three plants – water lily, nasturtium and sunflower. Privileged in this respect fragments of the façade are: the zone under the windows and doors (joinery and glazing) and the next in the order of occurrence of plant ornaments are frames and glazing of windows (stained glass).